ANALISIS PENAMBAHAN PHASE CHANGE MATERIAL PADA FLARED FIN HEATSINK MENGGUNAKAN COMPUTATIONAL FLUID DYNAMICS - Erzatama Aspriyanto, (2021)
Technological advancements enable manufacturers to produce high-performance electronic components in smaller sizes. Because of the restricted area provided, it is difficult to use active cooling technologies to remove the heat created by electrical components. Flared fin heatsink is one of the various types of heatsinks that have better performance than straight fin heatsinks under natural and force convection condition. Flared fin heatsinks are one of several types of heatsinks that outperform straight fin heatsinks under natural and forced convection conditions. Passive cooling systems utilizing an integrated heatsink with Phase Changed Material (PCM) have been developed in recent years. When compared to typical heatsink cooling systems, this design is capable of lowering the temperature of electrical components. The numerical simulation was used to investigate the influence of adding a paraffin-based PCM (RT-42) to the flared fin heatsink, as well as the effect of the number and thickness of fins on heat transfer performance and the melting process on the PCM-based heatsink. The results show that PCM is able to withstand the increase in base heatsink temperature during the melting process. The increase in the number and thickness of the fins speeds up the melting process and keeps the base heatsink at a lower temperature. Furthermore, the increased number of fins and heatsink fin thickness makes the convection transfer process more effective.